2019
DOI: 10.1039/c9gc00673g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotreatment of biocrudes derived from hydrothermal liquefaction and lipid extraction of the high-lipid Scenedesmus

Abstract: Biocrudes derived from hydrothermal liquefaction (HTL) and lipid extraction (EXT) of the high-lipid Scenedesmus were hydrotreated to investigate the influences of the feedstock on the profiles of the hydrotreating biofuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Consistent with other HTL wet-waste feedstocks, the upgraded product from biocrude derived from sewage sludge and food waste is rich in C 16 and C 18 nalkanes. 29,30 Most biological processes produce molecules, such as free fatty acids, which can be converted to n-C 16 and n-C 18 molecules through HTL and hydrotreating. Interestingly, both upgraded biocrudes derived from food waste had a higher ratio of C 18 n-alkanes to C 16 n-alkanes than HTL biocrude derived from sewage sludge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Consistent with other HTL wet-waste feedstocks, the upgraded product from biocrude derived from sewage sludge and food waste is rich in C 16 and C 18 nalkanes. 29,30 Most biological processes produce molecules, such as free fatty acids, which can be converted to n-C 16 and n-C 18 molecules through HTL and hydrotreating. Interestingly, both upgraded biocrudes derived from food waste had a higher ratio of C 18 n-alkanes to C 16 n-alkanes than HTL biocrude derived from sewage sludge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…HTL of palmitic acid (PA) at three different temperatures was conducted to support the above made hypotheses. PA was selected as model fatty acid as it has been widely confirmed as the major fatty acid in sewage sludge (Olkiewicz et al, 2012(Olkiewicz et al, , 2014Tang et al, 2019;Zhu et al, 2014), also identified from FAME as shown in Fig. 1.…”
Section: Htl Of Palmitic Acidmentioning
confidence: 99%
“…The investigation of ternary mixtures can be used to evaluate their potential bio-oil production via co-liquefaction. Furthermore, lipid extraction from waste biomass to be used for biodiesel increasingly becomes the focus of research [28,29]. How to effectively deal with the residues after extraction will most likely become a new challenge.…”
Section: Introductionmentioning
confidence: 99%